Evaluación de la Eficiencia en el Funcionamiento de la Planta de Tratamiento del Sistema de Agua Potable Regional Colatoa-San Marcos de la Parroquia Alaquez, cantón Latacunga. - Sánchez Alvarado, Edison Christian (2019)
The present investigation was carried out in the Colatoa-San Marcos regional drinking water treatment plant located in the Aláquez parish, Latacunga canton, Cotopaxi province, with the objective of determining the level of efficiency of water purification processes through physical-chemical and microbiological analyzes. For the evaluation of the efficiency of the treatment plant was taking as a starting point the sampling in two stages (summer and winter season), where two samples will be collected for each stage (entry and exit), which were subjected to physical-chemical and microbiological laboratory analyzes. The document collects the information of the aspects analyzed during the development of the work on the operation of the plant in order to establish the efficiency of purification processes based on the parameters established for the evaluation of each of the stages: Sedimentation, Filtration and Disinfection; were compared with the Ecuadorian Legislation in Force - NTE INEN 1108: 2014 Fifth revision (Maximum permissible limits for water for human consumption. The results obtained through the application of laboratory analysis determined that the conditions of the treated water are moderately good. This conclusion is taken because there are excesses in the parameters of turbidity, pH and iron in accordance with current Ecuadorian regulations. Based on these results, a redesign of the PTAP was proposed, where an aeration system with multiple trays was implemented, an increase of the retention time in the sedimentation process, a replica of a filtration tank and the implementation of dispensers with sensors for the entry control of the chemicals used (aluminum sulfate and hypochlorite).